Hubungan Dukungan Keluarga dengan Upaya Pencegahan Kekambuhan pada Penderita Hipertensi di Desa Cikembar Wilayah Kerja Puskesmas Cikembar Kabupaten Sukabumi - Rimba Febriana Saputra; Asmarawanti Asmarawanti; Yohan Frans Unmehopa (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Hypertension is a major global health problem with increasing prevalence and high risk of complications if not properly managed. One of the key factors influencing relapse prevention in hypertensive patients is family support. This study aimed to analyze the relationship between family support and relapse prevention efforts among patients with hypertension in Cikembar Village, Sukabumi Regency. The research employed a quantitative approach with a descriptive correlational design and cross-sectional method. A total of 288 respondents were selected using stratified random sampling. Data were collected using structured questionnaires, namely the Endrichd Social Support Instrument (ESSI) and the Hypertension Prevention Practices Questionnaire (HPPQ), and analyzed using chi-square statistical tests. The results showed that most respondents had supportive family environments (69.4%) and good relapse prevention practices (61.5%). Statistical analysis revealed a significant relationship between family support and relapse prevention efforts (p-value = 0.000). These findings indicate that strong family support plays an important role in improving patients’ adherence to healthy lifestyles and treatment plans. The study implies that health services should strengthen family-based interventions and educational programs to enhance hypertension management and reduce relapse risks.